Development of an articulated mobile robot moving on magnetic curved walls and passing over obstacles. (2nd November 2022) - Ueno, Shotaro; Nakajima, Mizuki; Tanaka, Motoyasu
Abstract : We developed an articulated mobile robot that can move on the magnetic curved walls and traverse through obstacles for wall surface inspections of a large tank. This robot is equipped with magnetic wheels and is able to stick to and move on steel wall. We add passive roll joints and turn off the torque of the pitch joints to ensure the wheels keep in contact with the curved surface. The developed robot is tested through experiments in the laboratory and also in a field test at the World Robot Summit 2020. The experiments are conducted to confirm the movements of the robot on the curved wall surface and when the units are lifted for obstacle traversal. As the results, the robot is not able to overcome an obstacle near the wall such as a handrail but is able to move freely on the curved wall surface and traverse some obstacles on the corner. GRAPHICAL ABSTRACT: UF0001